Integration of Culturally-Responsive Teaching in English Learning - Yuliantari, Shinta; Huda, Tanzil (Indonesian Journal Publisher, 2023)
This article explores the integration of culture-responsive teaching in English learning within the context of the new paradigm in education. As education systems become increasingly diverse and multicultural, there is a growing recognition of the importance of incorporating students' cultural backgrounds and experiences into the learning process. The new paradigm in education emphasizes a student-centered approach, where the focus is on promoting inclusivity, equity, and cultural competence in the classroom. Through a qualitative research design, this study examines the implementation of culture-responsive teaching in English language classrooms in a secondary school setting. Data were collected through classroom observations and interviews with teachers. The research aimed to understand how culture-responsive teaching practices are incorporated into English language instruction and the impact on student engagement and language proficiency. The findings indicate that the integration of culture-responsive teaching in English learning enhances student motivation and fosters a positive learning environment. By incorporating culturally relevant content and instructional strategies, teachers can create meaningful connections between students' cultural backgrounds and the language they are learning. This approach promotes a deeper understanding of language concepts and fosters a sense of belonging among students from diverse cultural backgrounds.